Daughters of Muscadine : stories - Ductan, Monic (Fireside Industries, 2023)
"Two events tie together the nine stories in Monic Ductan's gorgeous debut: the 1920s lynching of Ida Pearl Crawley and the 1980s drowning of a high school basketball player, Lucy Boudreaux. Both forever shape the people and the place of Muscadine, Georgia, in the foothills of Appalachia. The daughters of Muscadine are Black Southern women who are, at times, outcasts due to their race and also estranged from those they love. A remorseful woman tries to connect with the child she gave up for adoption; another, immersed in loneliness, attempts to connect with a violent felon. Two sisters love each other deeply even when they cannot understand one another. A little girl witnessing her father's slow death realizes her own power and lack thereof. A single woman weathers the excitement--and rigors--of online dating. Covering the last one hundred years, these are stories of people whose voices have been suppressed and erased for too long: Black women, rural women, Appalachian women, and working-class women. Ductan presents the extraordinary nature of everyday lives in the tradition of Alice Walker, Deesha Philyaw, James McBride, and Dorothy Allison in an engaging, engrossing, and exciting new voice"--